Enriching the Professional Development of Mathematics Teachers - Lee, Hea-Jin (ERIC digest., 2001)
In recent years there has been growing dissatisfaction with traditional approaches to teacher education. Educators have indicated that teacher education programs are not adequately preparing teachers for future conditions and student needs. The current focus of professional development includes not only teachers but also the many organizations to which they belong. This ERIC Digest focuses on recent strategies for enhancing professional learning as well as developing effective professional development models. Characteristics, critical issues, and strategies of professional development are provided as well as suggestions for the future. (Contains 12 references.) (MVL)